INVESTIGASI KEMAMPUAN BERNALAR ILMIAH SISWA MELALUI IMPLEMENTASI MODEL PROBLEM BASED LEARNING MATERI FISIKA FLUIDA STATIS - Ningrum, Tika Widiya; Handayani, Rif’ati Dina; Maryani, Maryani (Jurnal Pendidikan Fisika FKIP UM Metro, 2024)
In this 21st century, students are required to have skills in facing the challenges of globalization, one of which is scientific reasoning skills. Scientific reasoning is the ability to think systematically and logically to solve problems. Six indicators of scientific reasoning ability include conversion reasoning, proportional reasoning, variable control, probabilistic reasoning, correlation reasoning, and hypothesis-deductive reasoning. Scientific reasoning ability can be improved by using learning models that encourage students to think at a higher level, one of which is the Problem Based Learning (PBL) model. The purpose of this research is to determine the scientific reasoning ability of students through the application of the PBL model on static fluid physics material. This type of research is descriptive quantitative and qualitative. This research was conducted in class XI MIPA 4 SMAN 3 Jember. Data collection techniques in this study using observation techniques, interviews, tests, and documentation. Data analysis techniques in this study are data collection, data reduction, data presentation, data interpretation, and conclusion drawing. The results obtained are the average score of students' reasoning ability on the six indicators of scientific reasoning in the very good category. So it is concluded that the PBL model can improve students' scientific reasoning ability in static fluid physics material.